Hearing Screening in Infants in the Work Area Community Health Center - Anwar, Ahmad Ardhani Pratama; Arifuddin, Andi Tenri Sanna (Journal La Medihealtico, 2025)
The early discovery of hearing impairment among infants leads to essential intervention services which aid proper language and cognitive development. The administration of Otoacoustic Emission (OAE) screening stands as the primary testing method inside newborn and infant hearing screening programs throughout the world. Research on the implementation of Otoacoustic Emission testing in community health environments along resource-limited regions remains insufficient. The research investigated OAE hearing screening outcomes in Padanglampe Health Center infants from 24 months old through Padanglampe Health Center in Pangkep Regency including screening results and age and gender dynamics. The study used a cross-sectional observational approach with nine infants selected from a total group that satisfied the study criteria. OAE testing procedure served to screen the hearing of each participant. The researchers performed both descriptive and inferential analysis of gathered data. Fisher’s Exact Test evaluated the relationships between gender data along with screening outcomes and between different age intervals and their corresponding screening results. The calculations of odds ratios enabled investigators to determine how likely refer results occurred between male and female participants. The audiometric test with OAE technology showed positive results for eight out of nine screened infants but produced a refer outcome for the remaining one subject. A female infant under three months of age served as the subject in this refer case. Fisher’s Exact Test results demonstrated that gender and screening outcome relationship was non-statistically significant with a p value of 1.000 and results for age-based associations produced no significant findings.